Processing Of Liquid Waste From Dyeing Woven Yarns Using Activated Charcoal - Ramadani, Rizka Aulia; Rahmadina, Nazwa; Samsul Hadi (JFARM - Jurnal Farmasi, 2024)
Textile liquid waste containing various chemicals and pollutants is a serious problem because it is difficult to achieve waste water quality standards in accordance with Minister of Health Regulation No. 416/1990. This research uses a literature review method to analyze various studies related to the use of activated charcoal in treating industrial liquid waste. Activated charcoal, with a carbon composition of 85-95%, is known to have high adsorption capabilities thanks to its porosity which can reach hundreds to thousands of square meters per gram. The process of making activated charcoal involves carbonization and activation of carbon materials at high temperatures. The method used was a review of articles between 2015 and 2023. The research results showed that activated charcoal was effective in reducing Chemical Oxygen Demand (COD) by up to 98.74%, which indicates a significant reduction in pollutant content. The adsorption process, which is an exothermic reaction, occurs more efficiently at low temperatures and increases with the length of contact time between activated charcoal and liquid waste. Conclusion: Textile industry liquid waste and variations in activated charcoal dosage and shaking time provide concrete data on the efficiency of activated charcoal in dealing with water pollution, offering a sustainable solution for industrial liquid waste management.